The N Terminus of Human Cytomegalovirus Glycoprotein O Is Important for Binding to the Cellular Receptor PDGFRα - Stegmann, Cora (J Virol, 2019)
The human cytomegalovirus (HCMV) glycoprotein complex gH/gL/gO is required for the infection of cells by cell-free virions. It was recently shown that entry into fibroblasts depends on the interaction of gO with the platelet-derived growth factor receptor alpha (PDGFRα). This interaction can be blocked with soluble PDGFRα-Fc, which binds to HCMV virions and inhibits entry. The aim of this study was to identify parts of gO that contribute to PDGFRα binding. In a systematic mutational approach, we targeted potential interaction sites by exchanging conserved clusters of charged amino acids of gO with alanines. To screen for impaired interaction with PDGFRα, virus mutants were tested for sensitivity to inhibition by soluble PDGFRα-Fc. Two mutants with mutations within the N terminus of gO (amino acids 56 to 61 and 117 to 121) were partially resistant to neutralization. To validate whether these mutations impair interaction with PDGFRα-Fc, we compared binding of PDGFRα-Fc to mutant and wild-type virions via quantitative immunofluorescence analysis. PDGFRα-Fc staining intensities were reduced by 30% to 60% with mutant virus particles compared to wild-type particles. In concordance with the reduced binding to the soluble receptor, virus penetration into fibroblasts, which relies on binding to the cellular PDGFRα, was also reduced. In contrast, PDGFRα-independent penetration into endothelial cells was unaltered, demonstrating that the phenotypes of the gO mutant viruses were specific for the interaction with PDGFRα. In conclusion, the mutational screening of gO revealed that the N terminus of gO contributes to efficient spread in fibroblasts by promoting the interaction of virions with its cellular receptor. IMPORTANCE The human cytomegalovirus is a highly prevalent pathogen that can cause severe disease in immunocompromised hosts. Currently used drugs successfully target the viral replication within the host cell, but their use is restricted due to side effects and the development of resistance. An alternative approach is the inhibition of virus entry, for which understanding the details of the initial virus-cell interaction is desirable. As binding of the viral gH/gL/gO complex to the cellular PDGFRα drives infection of fibroblasts, this is a potential target for inhibition of infection. Our mutational mapping approach suggests the N terminus as the receptor binding portion of the protein. The respective mutants were partially resistant to inhibition by PDGFRα-Fc but also attenuated for infection of fibroblasts, indicating that such mutations have little if any benefit for the virus. These findings highlight the potential of targeting the interaction of gH/gL/gO with PDGFRα for therapeutic inhibition of HCMV.